Systematic Development of Sustainability-Oriented Cyber-Physical Production Systems - Rogall, Christopher; Mennenga, Mark; Herrmann, Christoph; Thiede, Sebastian (Sustainability, 2022)
Manufacturing companies increasingly have to address the risks and contributions related to their environmental impacts. Therefore, more data are needed in order to provide full transparency with regard to production, and to highlight the potential relationships between the process data and the environmental impacts. In order to achieve this data transparency, targeted digitalization is needed that is tailored to the goal of reaching minimized environmental impacts. Cyber-physical production systems (CPPSs) are central for the digitalization of manufacturing. However, they may also come with an initial environmental backpack. Due to unawareness of relevant interdependencies when setting up CPPS, data may be collected which is not helpful or necessary for the development of sustainability-oriented CPPS. Therefore, a critical assessment is required which data is necessary to support sustainable manufacturing and to avoid unreflective data collection. This requires the identification of the relevant factors and their interdependencies within the context of sustainability in production. By identifying the influencing factors, the measurement strategy can be linked to the appropriate sensor technologies that explicitly contribute to the target fulfillment. The design of more sustainable data structures using a cross-impact analysis is illustrated in this paper as a generic methodological approach, which will be applied to a 3D-printing use case.